2016
DOI: 10.1126/science.aaf3565
|View full text |Cite
|
Sign up to set email alerts
|

Filling in biodiversity threat gaps

Abstract: The diversity of life on Earth—which provides vital services to humanity (1)—stems from the difference between rates of evolutionary diversification and extinction. Human activities have shifted the balance (2): Species extinction rates are an estimated 1000 times the “background” rate (3) and could increase to 10,000 times the background rate should species threatened with extinction succumb to pressures they face (4). Reversing these trends is a focus of the Convention on Biological Diversitys 2020 Strategic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
163
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(175 citation statements)
references
References 10 publications
4
163
0
Order By: Relevance
“…Recently, Joppa et al (2016) have found that no global datasets are available for addressing IUCN listed pressures most affecting threatened marine species: "transportation and service corridors" and "human intrusions and disturbance". The catalogue contains indicators that tackle both issues (e.g., "Ballast water treatment indicator, " "Trends in pathways of introduction NIS").…”
Section: Capability To Address Pressuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Joppa et al (2016) have found that no global datasets are available for addressing IUCN listed pressures most affecting threatened marine species: "transportation and service corridors" and "human intrusions and disturbance". The catalogue contains indicators that tackle both issues (e.g., "Ballast water treatment indicator, " "Trends in pathways of introduction NIS").…”
Section: Capability To Address Pressuresmentioning
confidence: 99%
“…The DEVOTool catalogue of marine biodiversity indicators together with the DEVOTES catalogue on marine biodiversity monitoring networks compiled such information, and although it was evident that data are available, it is, nevertheless, difficult to evaluate its adequacy (e.g., Joppa et al, 2016) or account for this feature without a framework for properly ranking and selecting indicators.…”
Section: Recommendations For Future Improvements Of the Cataloguementioning
confidence: 99%
“…Better assessments of Eco-natural organic farming should conduct multidimensional long-term studies that consider local, regional, and global feedback between different variables (65)(66)(67)(68)(69). In addition, the representativeness of management practices used in studies requires attention (70)(71)(72)(73) have shown that relative Eco-natural yield performance is higher when best practices are used (120-125). Critics and advocates of Eco-natural organic farming describe (3,5) evidence of great uncertainty in many dimensions.…”
Section: Contextual Backgroundmentioning
confidence: 99%
“…Any new initiative to collate data needs to consider its role and define its niche within a complex environment of global, continental, national and regional data repositories [7,26]. Almost any effort to compile and harmonize data from these sources is impeded by differences in field names, definitions, and taxonomy, as well as access and license restrictions [3,27]. The use of common standards for all these aspects can improve the interoperability of these data sources: their data can be more efficiently exchanged, combined, compared, and presented.…”
Section: Improved Interoperability Of Information Sourcesmentioning
confidence: 99%